Comparison between the values of intra-ocular pressure measured by Goldmann applanation tonometer and Air-Puff non-contact tonometer and their relationship with central corneal thickness - Javed, Anum; Arshad, Muhammad Owais; Nasir, Javeria; Chatni, Muhammad Hanif; Ayub, Bushra (Journal of the Pakistan Medical Association, 2022)
Objective: Glaucoma is a sight threatening disorder. Measuring the IOP with accuracy plays a pivotal role in diagnosing and monitoring glaucoma. The purpose of this study was to compare the values of non-contact tonometer; air-puff and GAT (Goldmann Applanation Tonometer) along with its correlation to central corneal thickness (CCT), in various IOP (intra-ocular pressure) groups. Methods: Cross-sectional, prospective study. 311 patients were enrolled in this study. IOP was taken in all patients with APT and GAT. CCT was also measured. Data was analyzed and correlated with the help of Bland-Altman, Pearson correlation and intraclass correlation analysis regarding APT, GAT and CCT, using SPSS 24.0 software. Results: The median IOP measured by APT and GAT was 14mmHg (range: 37) and 12mmHg (range: 16) where as the median CCT was 534µ (range: 44), respectively. At low (<10mm of Hg) and normal IOP (10-20mm of Hg) both instruments showed similar results but at higher IOP (21-30mm of Hg) GAT is concluded more accurate (P=<0.001). Conclusion: GAT showed a high agreement with APT over a wide range of IOP. However, at moderate and higher group of IOP, APT revealed overestimation of IOP compared to GAT. CCT also plays a significant role. Continuous...